Computational Fluid Dynamics Studies of Hydrodynamic Parameters in a Two-Dimensional Conical Spouted Bed - Saeedi Razavi, Behzad; Hossein Hosseini, Seyyed (Asian Journal of Chemistry, 2012)
Hydrodynamics behaviour of a pseudo 2D conical spouted bed was studied by computational fluid dynamics code MFIX. Simulations were done in the symmetery two-dimensional frameworks using an Eulerian-Eulerian approach incorporating the kinetic theory of granular flows. Incoherent and steady spouting were analyzed and several hydrodynamic parameters were evaluated. Some parameters that influence the incoherent and steady spouting were investigated by the model. The validated model showed that nozzle diameter and inlet width are the important parameters on the hydrodynamics of the conical spouted beds. The simulation results showed that the computational fluid dynamics can be used as an effective tool to provide information on the details of particles behaviour in the conical spouted beds.